Draft Evidence by the Nursing Advisory Committee of the Trades Union Congress on nursing conditions & recruitment
1938-03-02 1938 1930s 9 pages PRIVATE & CONFIDENTIAL, NAT. ADV. C'CIL. FOR THE NURSING PROFESSION GOVT. ENQ. SUB. C'TEE. 3/1. 2nd March, 1938. TRADES UNION CONGRESS GENERAL COUNCIL. DRAFT EVIDENCE BY THE NURSING ADVISORY COMMITTEE OF THE TRADES UNION CONGRESS ON NURSING CONDITIONS & RECRUITMENT. Introduction. 1. The Trade Unions catering for Nursing grades, associated with the Trades Union Congress, have within their membership 25,000 of these grades. 2. For many years they have been viewing with disquietude the growing shortage of nurses in the various health services. They regard this shortage as due in the main to the unattractive comparison which girls of suitable educational qualifications make between this profession and the other vocations open to them at the conclusion of their school life. The shortage is undoubtedly accentuated by the increasing demand for Nursing owing to the development of various health services, but it is felt that this increased demand would be met to a very considerable extent if the Nursing profession was as attractive to the modern young woman as are other avenues which are open to her. 3. The principal thing to be done, therefore, is to modernise the conditions of the Profession and bring them up to the requirements of the average professional life of 1938. That the position will grow worse instead of better will be admitted when it is remembered that the birthrate of this country is decreasing whilst longevity is increasing. In the not too distant future, therefore, the number of young women eligible for entry into the profession will be smaller than at the present time, whilst the number of potential patients will be considerably greater. We consider that the relative unattractiveness of the Profession is proved by the fact that there is a greater number of entrants during times of economic depression than during periods of relative prosperity. The "Gap". 4. The fact that the profession is handicapped by unusual circumstances over which it has no control, makes it all the more urgent that reforms which can be instituted should be put into effect without delay. 5. One of the circumstances militating against recruitment into the profession is universally admitted to be the period which normally elapses between a girl leaving school and entering training at the age of 16. In the opinion of the Trade Unions this "gap" (as it is popularly called) should be overcome by the following methods. (a) Government grants should be extended for the purpose of training Nurses in the same way as Teachers and Doctors. Combined scholarship and maintenance grants should be offered to suitable girls between the ages of 16 and 18 on condition that their studies are vocational 292/54.73/2/18-22